Procoagulant changes in fibrin clot structure in patients with cirrhosis are associated with oxidative modifications of fibrinogen. (7th March 2016) - Hugenholtz, G. C. G.; Macrae, F.; Adelmeijer, J.; Dulfer, S.; Porte, R. J.; Lisman, T.; Ariëns, R. A. S.
Abstract : Essentials Patients with cirrhosis have hemostatic changes, which may contribute to a risk of thrombosis. This in vitro study compares clot formation and structure between patients and healthy subjects. Clot formation is delayed in patients; ultimately, however, clot permeability is decreased. The thrombogenic structure of fibrin clots may contribute to the thrombotic risk in cirrhosis. Abstract: Background and Objectives: Patients with cirrhosis can be at risk of thrombotic complications due to an imbalance between hemostatic components. However, little is known on how the disease affects clot generation or how alterations in the structure of fibrin clots may affect the hemostatic function of these patients. Methods: We investigated the formation and structure of clots generated with plasma and purified fibrinogen of 42 patients with cirrhosis. Clots generated with plasma and fibrinogen of 29 healthy volunteers were studied for comparison. Clot formation and structure were assessed by turbidity, permeation studies, confocal laser and scanning electron microscopy (SEM). The extent of fibrinogen oxidation was assessed by measuring the carbonyl content of purified fibrinogen samples. Results: Tissue factor and thrombin‐induced clotting of plasma was delayed in patients. The clotting rate was also decreased, but change in turbidity, fibrin density and fiber thickness were largely comparable to healthy volunteers. Conversely, clot permeability was significantly decreased in patients. When clots were generated with purified fibrinogen, differences in clot formation and structure similar to those in plasma were found. The carbonyl content was increased in patient fibrinogen and correlated with disease severity and clot permeability. Conclusions: Delayed clot formation in cirrhosis ultimately results in decreased clot permeability. Similar alterations in clots generated with purified fibrinogen suggest that modifications of the molecule are (partly) responsible. Taken together, these findings are indicative of hypercoagulable features of clots of patients with cirrhosis, which may explain the increased risk of thrombosis associated with this condition.